Climate, peace and security in Kenya - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
Communities across Kenya are navigating the dual threats of climate hazards and socio-political tensions. Severe droughts and floods, resource conflicts and evolving community roles - the impacts are far-reaching, especially in arid and semi-arid regions. Amidst these challenges, promising changes are taking root. Kenya's decentralized governance has empowered local communities, promoting inclusive decision-making and adaptive strategies to build resilience. This report, developed with insights from the CGIAR Climate Security Observatory examines how Kenya can guide climate action to promote cooperative resource management and reduce conflict risks.